A uniplanar manipulator for precision acoustic studies - T. Kamisiński; A. Flach (Archives of Acoustics)
Directional studies of acoustic systems and acoustic transducers require considerable precision of orientation combined with co-ordination of control and measurement processes. The paper describes a manipulator designed and built by the authors. The manipulator is so designed that it allows a studied sample to be precisely rotated with a remote control of the rotation angle. It makes it also possible to measure angle-dependent radiation and reception patterns of loudspeakers, microphones, antennas, noisy mechanisms etc. The method of control and data collection from the manipulator via an RS-232 port should also be noted. It is also possible to communicate with the plain table through LAN.